Computerized Cognitive Training for Older Adults at Higher Dementia Risk due to Diabetes: Findings From a Randomized Controlled Trial. (14th March 2019) - Bahar-Fuchs, Alex; Barendse, Marjolein E A; Bloom, Rachel; Ravona-Springer, Ramit; Heymann, Anthony; Dabush, Hai; Bar, Lior; Slater-Barkan, Shirel; Rassovsky, Yuri; Schnaider Beeri, Michal
Abstract: Background: To evaluate the effects of adaptive and tailored computerized cognitive training on cognition and disease self-management in older adults with diabetes. Methods: This was a single-blind trial. Eighty-four community-dwelling older adults with diabetes were randomized into a tailored and adaptive computerized cognitive training or a generic, non-tailored or adaptive computerized cognitive training condition. Both groups trained for 8 weeks on the commercially available CogniFit program and were supported by a range of behavior change techniques. Participants in each condition were further randomized into a global or cognition-specific self-efficacy intervention, or to a no self-efficacy condition. The primary outcome was global cognition immediately following the intervention. Secondary outcomes included diabetes self-management, meta-memory, mood, and self-efficacy. Assessments were conducted at baseline, immediately after the training, and at a 6-month follow-up. Results: Adherence and retention were lower in the generic computerized cognitive training condition, but the self-efficacy intervention was not associated with adherence. Moderate improvements in performance on a global cognitive composite at the posttreatment assessments were observed in both cognitive training conditions, with further small improvement observed at the 6-month follow-up. Results for diabetes self-management showed a modest improvement on self-rated diabetes care for both intervention conditions following the treatment, which was maintained at the 6-month follow-up. Conclusions: Our findings suggest that older adults at higher dementia risk due to diabetes can show improvements in both cognition and disease self-management following home-based multidomain computerized cognitive training. These findings also suggest that adaptive difficulty and individual task tailoring may not be critical components of such interventions. Trial registration: NCT02709629.